Histidine7.36(305) in the conserved peptide receptor activation domain of the gonadotropin releasing hormone receptor couples peptide binding and receptor activation. (15th February 2015) - Mayevu, Nkateko M.I.; Choe, Han; Abagyan, Ruben; Seong, Jae Young; Millar, Robert P.; Katz, Arieh A.; Flanagan, Colleen A.
Highlights: His 7.36(305) is proposed to couple GnRH receptor agonist binding with activation. Trp 3 is important for full agonist potency of the GnRH peptide. His 7.36(305) determines GnRH receptor recognition of Trp 3 of GnRH. Both His 7.36(305) and Trp 3 are required for full GnRH signaling potency. His 7.36(305) may indirectly couple Trp 3 binding to the receptor activation mechanism. Abstract: Transmembrane helix seven residues of G protein-coupled receptors (GPCRs) couple agonist binding to a conserved receptor activation mechanism. Amino-terminal residues of the GnRH peptide determine agonist activity. We investigated GnRH interactions with the His 7.36(305) residue of the GnRH receptor, using functional and computational analysis of modified GnRH receptors and peptides. Non-polar His 7.36(305) substitutions decreased receptor affinity for GnRH four- to forty-fold, whereas GnRH signaling potency was more decreased ( 150-fold). Uncharged polar His 7.36(305) substitutions decreased GnRH potency, but not affinity. [2-Nal 3 ]-GnRH retained high affinity at receptors with non-polar His 7.36(305) substitutions, supporting a role for His 7.36(305) in recognizing Trp 3 of GnRH. Compared with GnRH, [2-Nal 3 ]-GnRH potency was lower at the wild type GnRH receptor, but unchanged or higher at mutant receptors. Results suggest that His 7.36(305) of the GnRH receptor forms two distinct interactions that determine binding to Trp 3 and couple agonist binding to the conserved transmembrane domain network that activates GPCRs.